Mirabegron for intramural ureteral stones with vesical irritability: a prospective study - Dai, Mengjun; She, Yuhang; Wang, Hao (Frontiers in Pharmacology, 2025)
ObjectiveTo assess the efficacy of mirabegron in patients with intramural ureteral stones (6–10 mm).MethodsWe prospectively randomized 92 patients with intramural ureteral stones into two groups. Patients in the mirabegron group received 50 mg of mirabegron daily, while those in the tamsulosin group received 0.4 mg tamsulosin daily. All patients were required to use the Urinary Sensation Scale (USS) to assess the urinary urgency and the Visual Analog Scale (VAS) to assess pain. Patients were followed until stone expulsion or for up to 4 weeks.ResultsAll of 80 patients were included in this study. 41 patients in mirabegron group and 39 patients in tamsulosin group as control. The average expulsion time was shorter in mirabegron group than in tamsulosin group (8.4 ± 2.9 vs. 11.2 ± 3.1 days, P < 0.0001). The stone expulsion rate (SER) was higher in mirabegron group than in tamsulosin group on 1 and 2 weeks (36.6% vs. 15.4%, P = 0.031 and 75.6% vs. 43.6%, P = 0.004). However, the SER on 4 weeks had no statistical difference between two groups (P > 0.05). Post-treatment VAS and USS scores were lower in mirabegron group than tamsulosin group (P < 0.05).ConclusionMirabegron not only accelerates the expulsion of intramural ureteral stones but also relieves renal colic and vesical irritability.